1977
DOI: 10.1007/bf00996330
|View full text |Cite
|
Sign up to set email alerts
|

Persistent metabolic abnormalities in diabetes in the absence of glucagon

Abstract: In order to investigate the contribution of glucagon to the abnormalities of carbohydrate and lipid metabolism in diabetes, hormones and metabolites were measured in response to IV arginine in 5 juvenile onset (control) diabetics and 5 totally pancreatectomised subjects. In the basal state, both control diabetics and pancreatectomised patients showed abnormally elevated levels of plasma glucose, blood 3-hydroxybutyrate, glycerol and plasma free fatty acids (NEFA), although no glucagon was detectable in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Plasma glucagon measurements in pancreatectomized human subjects have yielded conflicting results: zero values were reported by Barnes~et al [46], while other groups reported significant IRG levels in these patients (review in [47]), and even, a glucagon response to an arginine infusion [48]. In any case, a crucial experiment was reported in which the importance of glucagon in the development of diabetic hyperglycaemia and ketoacidosis was evaluated by withholding insulin from six patients with juvenile-type diabetes and four totally pancreatectomized subjects [49].…”
Section: Does Endogenous Glucagon (In Absolute or Relative Excess) Plmentioning
confidence: 96%
“…Plasma glucagon measurements in pancreatectomized human subjects have yielded conflicting results: zero values were reported by Barnes~et al [46], while other groups reported significant IRG levels in these patients (review in [47]), and even, a glucagon response to an arginine infusion [48]. In any case, a crucial experiment was reported in which the importance of glucagon in the development of diabetic hyperglycaemia and ketoacidosis was evaluated by withholding insulin from six patients with juvenile-type diabetes and four totally pancreatectomized subjects [49].…”
Section: Does Endogenous Glucagon (In Absolute or Relative Excess) Plmentioning
confidence: 96%
“…with a plasma stripped of glucagon by affinity chromatograp n y [13][14][15] On the other hand, it is now well accepted that the 30K antiserum not only measures true glucagon (IRG 3500 ) but also a family of polypeptides, including a large molecular weight substance of unknown origin, BPG, 42 -43 9000-21,000-daltoii polypeptides likely to represent glucagon precursors, 44 " 49 as well as a small 2000 mol. wt.…”
Section: Minutes Figure 3 Insulin Withdrawal In Four Pancreatectomizmentioning
confidence: 99%
“…First, the studies by Barnes and Bloom in totally pancreatectomized patients have shown that the metabolic abnormalities of diabetes can occur in the absence of detectable circulating glucagon. 13 " 15 However, plasma glucagon measurements in pancreatectomized human subjects have yielded conflicting results: if, indeed, undetectable values were reported by Barnes and Bloom 13 and Gerich et al, 16 other groups reported significant IRG levels 17 " 25 and in a few patients, a glucagon response to an arginine infusion has been described. 22 -23 Thus, both the existence of an extrapancreatic source of glucagon in man and the necessary presence of glucagon for the development of hyperglycemia remain in dispute.…”
mentioning
confidence: 99%
“…On the other, the question of whether or not plasma ofhumans without pancreas retains near-normal basal levels of glucagon remains controversial. In a previous study, Muller et al (16) found basal glucagon values of 35 pg/ml, whereas Barnes et al (17,18) 30-K in distinct fractions of plasma obtained from duodenopancreatectomized patients, both in the basal state and after an arginine infusion; brings new facts and, hopefully, some answers. This study also examined the possibility that glucagon-like immunoreactivity (GLI) from the gut might be elevated in the plasma of patients without pancreas, as shown by Matsuyama and Foa in pancreatectomized dogs (13).…”
Section: Introductionmentioning
confidence: 97%
“…On the one hand, there is agreement that, in these patients, arginine fails to elicit an increase in plasma glucagon (16)(17)(18), even though such an increase is readily seen in insulindeficient pancreatectomized dogs (11)(12)(13)(14)(15)19). On the other, the question of whether or not plasma ofhumans without pancreas retains near-normal basal levels of glucagon remains controversial.…”
Section: Introductionmentioning
confidence: 99%